3D‐Printed PCL/rGO Conductive Scaffolds for Peripheral Nerve Injury Repair. Issue 5 (12th November 2018) - Vijayavenkataraman, Sanjairaj; Thaharah, Siti; Zhang, Shuo; Lu, Wen Feng; Fuh, Jerry Ying Hsi
Abstract: The incidence of peripheral nerve injuries is on the rise and the current gold standard for treatment of such injuries is nerve autografting. Given the severe limitations of nerve autografts which include donor site morbidity and limited supply, neural guide conduits (NGCs) are considered as an effective alternative treatment. Conductivity is a desired property of an ideal NGC. Reduced graphene oxide (rGO) possesses several advantages in addition to its conductive nature such as high surface area to volume ratio due to its nanostructure and has been explored for its use in tissue engineering. However, most of the works reported are on traditional 2D culture with a layer of rGO coating, while the native tissue microenvironment is three‐dimensional. In this study, PCL/rGO scaffolds are fabricated using electrohydrodynamic jet (EHD‐jet) 3D printing method as a proof of concept study. Mechanical and material characterization of the printed PCL/rGO scaffolds and PCL scaffolds was done. The addition of rGO results in softer scaffolds which is favorable for neural differentiation. In vitro neural differentiation studies using PC12 cells were also performed. Cell proliferation was higher in the PCL/rGO scaffolds than the PCL scaffolds. Reverse transcription polymerase chain reaction and immunocytochemistry results reveal that PCL/rGO scaffolds support neural differentiation of PC12 cells.